Possibilidades interpretativas em Psappha de Iannis Xenakis - Sergio Francisco Braga Aluotto (2011)
The main goal of this paper is to survey the interpretive possibilities for Psappha by Iannis Xenakis, a multiple percussion solo piece whose graphic score, along with the instructions on the Explanatory Note, provides several openings for the participation of the performer. Given the historical importance of the work and compositional innovations by Xenakis, this important solo has been widely presented since its composition, resulting in very distinct performances. However, after searching for related studies and analyzing performances, it was observed that some of the interpretive possibilities inherent to the score have been little explored. In order to speculate on such possibilities, this study sought, through a musical analysis combined with performance practices, to propose instrumentation and techniques that could enable the interpretation of the different meanings attributed to the accents in Psappha, poorly explored until now. As a result of this study, I will present considerations concerning the various nalyses of the work and performance records studied. Moreover, I will share further notes, possibilities and technical solutions devised from personal interpretive studies.